Animal families - Stuart, Gene S. (Washington, D.C. : National Geographic Society, 1990)
Text and pictures present families of different kinds of animals doing their ordinary activities.
Includes bibliographical references (p. [34]).
Keywords: Familial behavior in animals -- Juvenile literature; Animals -- Juvenile literature; Familial behavior in animals; Animals